Implementasi Nilai-nilai Moderasi Beragama Melalui Kegiatan Seminar Keagamaan di Mesjid Al-Qauman Desa Gunung Melayu - Isnanda Ayu Misriyah; ma Lia Putri; Rahmad Diki Zulkarnain; Ahmad Ramadhani; Susilawati Susilawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Implementation of religious moderation starts early, since this age fitting for fundamental schooling to get used to providing moderate religious values, when the upsides of strict control can be applied in basic islamic education. Namely a religious seminar with an expansive structure a strict control. The reason for this study is to look at the execution of strict control values conducting religious seminar activities at Al Qauman Mosque in Gunung Melayu Village.One of the places is in north Labuhanbatu district, Gunung Melayu Village, Hamlet II Kampung Lalang. Data collectionwas carried out bye observation and bye inteviewing Ustadz and communityof Gunung Melayu Village. The results of this study are: Through the religious seminar activities carried out in Village of Gunung Melayu, it can build religious understanding for young children and adolescents, especially the Gunung Melayu communityto become more moderate and can strengthen community religious moderation. Religious seminars and da’wah activities from the delivery of clerics as speakers of religious seminars build awareness that reflects values of religious moderation and get used to being adisciplined and istiqomah society with worship. Keywords:Implementation,Religious Moderation, Religious Seminars